2020
DOI: 10.1088/1361-6463/abaaa6
|View full text |Cite
|
Sign up to set email alerts
|

Towards model-driven reconstruction in atom probe tomography

Abstract: Reconstructions in atom probe tomography (APT) are plagued by image distortions arising from changes in the specimen geometry throughout the experiment. The simplistic and inaccurate geometrical assumptions that underpin the conventional reconstruction approach account for much of this distortion. Here we extend our previous work of modelling APT experiments using level set methods to three dimensions (3D). This model is used to generate and subsequently reconstruct synthetic APT datasets from electron tomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 20 publications
(41 citation statements)
references
References 45 publications
0
41
0
Order By: Relevance
“…This leaves only the evaporation field of the NP and coating as parameters in an otherwise well-characterized system. These parameters may be iteratively optimized to reproduce features from EM (Fletcher et al, 2020).…”
Section: Specimen Preparation Potential and Limitationsmentioning
confidence: 99%
“…This leaves only the evaporation field of the NP and coating as parameters in an otherwise well-characterized system. These parameters may be iteratively optimized to reproduce features from EM (Fletcher et al, 2020).…”
Section: Specimen Preparation Potential and Limitationsmentioning
confidence: 99%
“…Sub-nanometer spatial and isotopic resolution, as well as the ability to measure millions of ions, makes APT a unique tool for characterizing the nanoscale composition of bulk material volume (Kelly & Miller, 2007;Vurpillot et al, 2017;Saxey et al, 2018) or quantifying the chemical decoration of crystal defects with solute atoms (Leitner et al, 2017;Stoffers et al, 2017;Ghamarian & Marquis, 2020;Zhou et al, 2021). These capabilities, especially, when used in correlation with electron microscopy (Herbig et al, 2015;Breen et al, 2017;Eder et al, 2018;Fletcher et al, 2020), substantiate that APT and FIM are useful techniques for quantitatively characterizing microstructure-material-property correlations.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a reconstruction approach based on an analytical description of the emitter curvature for axial symmetric cases of bilayers (Rolland et al, 2015a) and multilayers (Rolland et al, 2015b) has been proposed. Another promising reconstruction approach by Fletcher et al (2020) utilizes a 3D continuum modeldriven reconstruction algorithm. Most recently, Beinke & Schmitz (2019) and Beinke et al (2020) demonstrated a concept to extract the real shape of the emitter directly from the event density on the detector that is applicable to sample surfaces of almost arbitrary shape.…”
Section: Introductionmentioning
confidence: 99%